2021
DOI: 10.31000/combis.v3i2.8326
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Pertumbuhan Laba Dengan Menggunakan Rasio Camel Pada Perbankan Syariah Di Indonesia Tahun 2017 – 2021

Abstract: Tujuan dari penelitian ini untuk mengetahui determinan pertumbuhan laba dengan menggunakan rasio CAMEL (rasio CAR, NPF, NPM, BOPO dan FDR) pada perbankan syariah di Indonesia. Periode penelitian yang digunakan adalah 5 tahun yaitu periode 2017 – 2021.Populasi penelitian meliputi semua perbankan syariah di Indonesia periode 2017 – 2021. Teknik pengambilan sampel menggunakan teknik purposive sampling. Berdasarkan kriteria yang telah ditetapkan diperoleh jumlah sampel 11 perusahaan. Jenis data yang digunakan adal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…However, the result of this study indicated that the NPM variable did not affect Bank Muamalat's net profit. These results were consistent with Siregar &Hamdani, (2019), andHidayati &Purwitosari (2020), which stated that Net Profit Margin did not affect profit growth. This study's results contradicted the research Salhuteru & Wattimena (2015), which stated that Net Profit Margin had a positive effect on earnings management.…”
Section: Net Profit Margin On Net Profitsupporting
confidence: 90%
“…However, the result of this study indicated that the NPM variable did not affect Bank Muamalat's net profit. These results were consistent with Siregar &Hamdani, (2019), andHidayati &Purwitosari (2020), which stated that Net Profit Margin did not affect profit growth. This study's results contradicted the research Salhuteru & Wattimena (2015), which stated that Net Profit Margin had a positive effect on earnings management.…”
Section: Net Profit Margin On Net Profitsupporting
confidence: 90%